DESIGNING AN INFORMATION SYSTEM SIMULATION OF PSYCHOLOGICAL TEST QUESTIONS USING THE C4.5 METHOD AT THE WEB-BASED HRC LAVANDA PSYCHOLOGY BUREAU - Rini Wulandari; Charles Jhony Mantho Sianturi (Kresnamedia Publisher, 2022)
Abstract Psychological tests or psychological tests are a diagnostic effort with specific measuring tools created by psychologists to reveal a picture of a person's potential or to distinguish a person's behaviour from others through particular problems. Not all psychological tests can be easily computerized, and an accounting application can be easily modelled mathematically. At the very least, it must be admitted that at this time, there are very few psychological tests in Indonesia that are well computerized. It will be troublesome if the test is intended for recruitment purposes, especially if the company concerned needs the test results as quickly and accurately as possible. Seeing this background, the author wants to help and provide easy solutions by utilizing the internet media, a field of information and media that is very useful for everyone. The C4.5 method is applied to classify personality test questions, interest aptitude tests, SPM tests, and arithmetic tests to produce accurate calculations for the classification of psychological test questions. With the information system for the psychological test questions using the C4.5 method, it is hoped that the public can more easily access the simulated psychological test questions easily and quickly.